ANATOMY OF THE DIGESTIVE SYSTEM ORGANS AND THEIR INTERRELATIONSHIPS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The digestive system is a complex network of organs responsible for the ingestion, digestion, absorption, and elimination of food substances. This article examines the anatomical structure of digestive organs and their functional interrelationships. The study highlights how coordinated interactions among organs such as the mouth, esophagus, stomach, intestines, liver, pancreas, and gallbladder ensure efficient digestion and nutrient absorption. A comprehensive understanding of these relationships is essential for medical education, clinical practice, and the diagnosis of gastrointestinal disorders.